2014
DOI: 10.1021/jm500997m
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Activities of Propolis and Its Promising Component, Caffeic Acid Phenethyl Ester, against Amyloidogenesis of Human Transthyretin

Abstract: Transthyretin (TTR) is a homotetrameric serum protein associated with amyloidoses such as familial amyloid polyneuropathy and senile systemic amyloidosis. The amyloid fibril formation of TTR can be inhibited through stabilization of the TTR tetramer by the binding of small molecules. In this study, we examined the inhibitory potency of caffeic acid phenethyl ester (CAPE) and its derivatives. Thioflavin T assay showed that CAPE suppressed the amyloid fibril formation of TTR. Comparative analysis of the inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 56 publications
5
56
0
Order By: Relevance
“…[21] As shown in Figure 5 i, the docking pose calculated for wild-type TTR (sky blue) was very similar to the experimental pose (green, from the V30M TTR-ROA complex, PDB ID: 4PWI). The good interaction was supported through a very high docking score.…”
Section: Dockingsupporting
confidence: 57%
“…[21] As shown in Figure 5 i, the docking pose calculated for wild-type TTR (sky blue) was very similar to the experimental pose (green, from the V30M TTR-ROA complex, PDB ID: 4PWI). The good interaction was supported through a very high docking score.…”
Section: Dockingsupporting
confidence: 57%
“…Similar activities were observed for caffeic acid ethylester (18). This compound showed antihypertensive, antioxidant and anti-inflammatory activities that can be connected with usage of Ziziphora against diseases of cardiovascular system [101][102][103][104][105][106][107][108][109][110][111][112]. Similarly, rosmarinic acid (19) possesses various activities, also connected with civilization diseases like cardiovascular system illnesses, chronic inflammations and cancer [113][114][115][116].…”
Section: Omementioning
confidence: 71%
“…Caffeic acid (17) Z. clinopodioides [80] Anticancer potential reviewed [98] Protection of endothelial cells (review by Fuentes and Palomo [99]) General review on applications [100] O H O OH Ethyl ester of caffeic acid (18) Z. clinopodioides [4] Weak inhibitory activity on NO production stimulated by LPS and IFN-γ in RAW 264.7 cells [4] Antihypertensive [101,102] Anti-inflammatory [103][104][105] Antidiabetic [106] Inhibitory activity against amyloidogenesis [107] Antioxidative [108][109][110][111] Anticancer [112] O H…”
Section: O-glc Hmentioning
confidence: 99%
“…In 2014, we also found that caffeic acid phenethyl ester (CAPE) from New Zealand propolis inhibits TTR amyloid fibril formation. 19) Some compounds found in common and functional foods have also been identified as TTR amyloidogenesis inhibitors. Curcumin from turmeric and xanthohumol from hops were shown to inhibit TTR amyloid fibril formation in 2009 and 2010, respectively.…”
Section: Takeshi Yokoyama Graduated From the School Of Engineering Scmentioning
confidence: 99%
“…Amyloid fibril disaggregation assays were performed as described previously. 19) Briefly, preformed TTR amyloid fibrils were incubated in the presence of 10 or 50 µM of the compounds for 5-6 h, and the extent of amyloid fibril formation was quantified using a thioflavin T assay (excitation: 440 nm; emission: 484 nm).…”
Section: (A-g) Competitive Binding Assays Of the Selected Compoundsmentioning
confidence: 99%